Access audit on universal design: the case of Kota Kinabalu waterfront - Abdullah, Fadzidah; Abdul Rahim, Asiah (2010)
Most developed countries have enforced the use of “Universal Design” in any physical development of their cities, for the purpose of eliminating discrimination among the society members towards the unfortunate handicapped persons. Nevertheless, in many developing countries, the awareness and inclusion of Universal Design is still in its initial stage. Cities’ authorities have not fully enforced the requirement of providing access to people with disability in their built environment; neither in public nor private spaces. The Department of Standard Malaysia (SIRIM) had initiated the publication of Malaysian Standards as guidelines for designers; architects, city planners, landscape architects, interior designers, and others who are involved in the construction of physical development with Universal Design.